2012
DOI: 10.1080/01635581.2012.630163
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Prostate Cancer Prevention: A Review of Observational Studies by Focusing on South America

Abstract: There exist several works considering the association between diet and prostate cancer (PC) risk, but the issue is largely unsettled. This article systematically reviews the epidemiological studies on diet and risk of PC focusing on those carried out in countries of South America. There is some suggestion that dairy products, red meat, processed meat, α-linolenic fatty acids, as well as dietary patterns characterized by higher intakes of red and processed meat, eggs, and grains may play some role in the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 123 publications
0
17
0
Order By: Relevance
“…Prostate cancer is the second most common cancer in men worldwide, and it also ranks second in men in South America . Obesity, central adiposity, and several dietary factors have been suggested as risk factors.…”
Section: Obesity and Comorbiditiesmentioning
confidence: 99%
“…Prostate cancer is the second most common cancer in men worldwide, and it also ranks second in men in South America . Obesity, central adiposity, and several dietary factors have been suggested as risk factors.…”
Section: Obesity and Comorbiditiesmentioning
confidence: 99%
“…High intakes of some foods, such as dairy products, red meats, and processed meats, have been suggested as possible risk factors. Additionally, nutrients including α -linolenic acid and calcium seem to play a role in prostate carcinogenesis [ 6 ]. Despite the increasing number of published papers addressing the relationship between dietary habits and PC from different approaches, the issue is still open to discussion.…”
Section: Introductionmentioning
confidence: 99%
“…The role of dietary fats on the risk of prostate cancer is controversial [7]. South American studies showed that only α-linolenic acid influenced the progression of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%